Phytotoxic effects of Melia azedarach L. (Meliaceae) fruit extract on weeds and crops - Palacios, Sara Maria (2009)
In our continuous search for bioactive products obtained from plants with agrochemical prospects, the extract of Melia azedarach L. fruits was tested for the phytotoxicity against weeds and crops. In a paper disk assay, this extract inhibited the seed germination of Avena sativa L., Brassica napus L., Chenopodium album L., Lactuca sativa L. and Sorghum halepense L. (Pers) and the 50% germination inhibitory doses (GID50) were 0.27, 16.5, 2.88, 7.85 and 1.31 mg/ml, respectively. Melia fruit extract also inhibited the seedling growth and 50% growth inhibitory doses (GrID50) were 0.59, 1.86, 5.59, 3.98 and 1.03 mg/ml, respectively. The effects of crushed M. azedarach fruit material mixed with the soil were examined on germination, radicle and shoot length of A. sativa and S. halepense in assay for 30 days. A GID50 of 0.56 and 3.51 % (w/w) was determined for A. sativa and S. halepense, respectively, while 10 % (w/w) concentration completely inhibited the root and shoot length in both species. These results indicate that phytotoxic compounds are present in M. azedarach fruits.